Media Framing of COVID-19: A Content Analysis of Nepali Newspapers - Dahal, Sudhamshu; Khatri, Bishnu Bahadur (Nepalese Journal of Development and Rural Studies, 2021)
The COVID-19 pandemic has spread across the globe, posing a major and alarming public health concern. This has been due, in part, to the increasing number of infected population day by day. Also, media coverage appeared to be one of the influencing factors to the opinion formation of COVID-19 issues. Since the whole world is still reeling under the effect of COVID-19 pandemic. At this juncture, the content and tone of the newspaper is still unknown. Therefore, the paper tries to assess critically about the media effect in reporting of the COVID-19 pandemic. This study has a significant practical relevance during this period. Furthermore, the study contributes to scientific knowledge about the use of frames and tones in media coverage with regard to pandemic. For this purpose and use of a content analysis, two popular Nepalese English language newspapers; The Kathmandu Post (privately owned media) and The Rising Nepal (state-owned media) has been selected purposively. The content and tone of the media coverage with regard to the pandemic from May 2020 until the end of July 2020 was investigated. The results showed that the media coverage was most frequently done in terms of economic crisis rather than covering the pandemic as a health crisis. Furthermore, the tone of the media coverage of the pandemic is more negative in the privately owned media than the state-owned media. However, both the newspapers have covered the majority of articles through the economic framing rather than health.